Motivation in the Organization - Livianti, Laudy; Hayati, Fitri (Indikator Pendidikan Indonesia, 2022)
In an organization, motivation plays an important role because it is directly related to the causes of the human part of the organization. With the right motivation, the organization can be further promoted and expanded. The human part of the organization consists of two groups of people, namely those who lead and those who are led. The issue of motivation in organizations is the responsibility of management, organizing and implementing. Therefore, management should create motivation according to the type of motivation, e.g. the fact that people's motives for action are capable of motivating people's motives to want to act in accordance with the wishes of the organization.